Curricula framework for a digital transformation master’s in science and engineering (2021)
Digital transformation is an interdisciplinary work that has the objective to analyze data in real-time for better decision making, where it involves the modeling and the simulation of physical-mathematical and social processes and the monitoring of machinery that using information and communication technologies. Nowadays the fourth industrial revolution technologies are the driver for this transformation and soon will be quantum computing and other physics and mathematics advances. Therefore, in this academic-scientific work, a curricular framework is proposed for a master's program in digital transformation for science and engineering; the framework follows the literature review and analysis to formulate the denomination and justification for the master's degree. The results are (i) a general three-level model as a roadmap for the specific curricular design of a master’s in digital transformation for science and engineering; (ii) the recommendation that a master's program has a research focus in the two categories established by the Colombian standard (research and practitioner); (ii) finally, a political, economic, social, technological, environmental, and legal analysis justifies a master’s in digital transformation for science and engineering. The research model details the phases that were carried out to characterize and identify the curriculum framework that will be the basis for formalizing the master's degree document.